Novel engineered B lymphocytes targeting islet-specific T cells inhibit the development of type 1 diabetes in non-obese diabetic Scid mice - Chen, Dawei; Kakabadse, Dimitri; Fishman, Sigal; Weinstein-Marom, Hadas; Davies, Joanne; Boldison, Joanne; Thayer, Terri C.; Wen, Li; Gross, Gideon; Wong, F. Susan (Frontiers in Immunology, 2023)
In this study, we report a novel therapeutic approach using B lymphocytes to attract islet-specific T cells in the non-obese diabetic (NOD) mouse model and prevent the development of autoimmune diabetes. Rather than use of the antibody receptor of B cells, this approach utilizes their properties as antigen-presenting cells to T cells. Methods: Purified splenic B cells were treated with lipopolysaccharide, which increases regulatory B (Breg) cell function, then electroporated with mRNA encoding either chimeric MHC-I or MHC-II molecules covalently linked to antigenic peptides. Immunoregulatory functions of these engineered B cells (e-B cells) were tested by in vitro assays and in vivo co-transfer experiments with beta-cell-antigen-specific CD8 + or CD4 + T cells in NOD.Scid mice respectively. Results: The e-B cells expressing chimeric MHC-I-peptide inhibited antigen-specific CD8 + T cell cytotoxicity in vitro. The e-B cells expressing chimeric MHC-II-peptide induced antigen-specific CD4 + T cells to express the regulatory markers, PD-1, ICOS, CTLA-4, Lag3 and Nrp1. Furthermore, e-B cells encoding the chimeric MHC-I and MHC-II peptide constructs protected NOD.Scid mice from autoimmune diabetes induced by transfer of antigen-specific CD8 + and CD4 + T cells. Discussion: MHC-peptide chimeric e-B cells interacted with pathogenic T cells, and protected the host from autoimmune diabetes, in a mouse model. Thus, we have successfully expressed MHC-peptide constructs in B cells which selectively targeted antigen-specific cells, raising the possibility that this strategy could be used to endow different protective cell types to specifically regulate/remove pathogenic cells.